PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA III (PERSERO) - M Basri Kamal (Universitas Muhammadiyah Sumatera Utara, 2018)
Based on the research results it can be concluded that the leadership effect on work discipline. Supervision of work discipline. From the calculation, that affect the leadership and supervision of work discipline. The most dominant variable influence on the discipline of work is variable supervision. Keywords: Leadership, Supervision and to Discipline Employees